Desnutrición en menores de cinco años hospitalizados en el área de pediatría del Hospital Teófilo Dávila desde diciembre 2007 a mayo 2008 - Torres Arévalo, Bheidy M. (2008)
This present descriptive study, was carried out through direct observation and surveys applied to mothers of 242 children of less than 5 years of age hospitalized in the area of pediatrics at the Teofilo Davila Hospital in Machala city from December 2007 until May 2008, whose objective of which was to determine the incidence of malnutrition, its characteristics and the most outstanding factors that influence in this pathology. We conclude that 44% of the registered cases at the pediatrics area belong to malnourished children, having a larger frequency those children less than a year of age, prevailing the males over females, and those in families of low socioeconomic and educational level.